Prevalence and Clinical Characteristics of Depression among Elderly Patients Attending Primary Health Care Centers in Diyala Governorate - Fadhil, Abeer Y.; Hashim, Mushtaq T. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Depression is one of the most common mood conditions among the elderly, which is linked to severe consequences such as difficulty in concentration and mood disturbances, followed by a lack of interest in social activities, apathy, pessimism, and changes in appetite and sleep.Aim of the study: To determine the prevalence and clinical characteristics of depression and the associated factors among 60-year-olds and over.Methodology: A descriptive cross-sectional study conducted on a group of 218 patients attending selected primary health care centers (PHCC) in Diyala governorate from Al-Khales and Baquba first sectors from first of September 2020 till first of April 2021. A direct interview was conducted by the researcher. Depression in the studied group was measured using the Arabic version of the short form of Geriatric Depression Scale (GDS). Socio-demographical factors were also inquired about in this study.Results: The prevalence of depression among the study participants was 63.3%. There was a statistically significant association between depression and gender (higher in females 69.2%), marital status (in widowed 84.8%), current residence (93.3% in those living alone), and source of monthly income (78.1% in those on financial assistance), medical illnesses (70.2%), and past history of depression (71.3%).Conclusions: Depressive symptoms are prevalent among elderly patients attending primary health centers in Diyala Governorate and are associated with female gender, being a widow, living alone, financial insecurity and chronic illnesses.